Pengaruh E-Filing Terhadap Penerimaan Pajak Penghasilan Wajib Pajak Badan - Risna Rahmawati; Siti Mialasmaya; Robbi Saepul Rahman; Vicky Achmad Zulfikar (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
This study aimed to determine the effect of e-Filing on Corporate Taxpayer income tax receipts at one KPP in Bandung. The research method used is descriptive and verification research methods at one of the KPP in Bandung. To obtain data and information that will support this research, namely by collecting primary data and an in-depth description of the effect of e-Filing on the income tax revenue of Corporate Taxpayers. The results showed that the correlation analysis resulted in a coefficient of 0.705, which include in the strong category. The regression estimation result is 15,581; this shows the value of Corporate Taxpayer income tax revenue. If e-Filing increases by units, the acquisition of tax revenue will increase by 12.59 units. A positive sign indicates that the better the e-Filing, the higher the income tax revenue. The importance of the coefficient of determination of 0.496, which indicates that e-Filing affects the income tax revenue of Corporate Taxpayers by 49.6%, and the remaining 50.4% is the influence of other factors not examined by the author, such as compulsory compliance with Corporate Taxpayers at one of the KPP in Bandung.